(untitled) (REVISTA ECUATORIANA DE CIENCIAS SOCIALES Y JURÍDICAS, 2017)
The transformations that have taken place since the end of the Cold War on the security field have triggered new risks and threatswhich mustbe understood from a multidimensional perspective. Thus, in a globalized and interconnected world, the interest for security threats and crisis management has increased considerably. In that sense, this paper aims to present the West African region as a key strategic actor in today’s international community. On the one hand, it has gained importance in the last years due to its economic, commercial, and demographic potential. On the other hand, it encompasses a series of threats to security, which have a destabilization power throughout the region, but also an international range, such as terrorist and rebel group acts, illicit trafficking routes to Europe or internal convulsions in those weak African states, which affect not only African countries but also international security. The increasing tensions in this area stress the fact that preventive measures tackling the root causes of violence are not effective enough.